(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
In the context of contemporary thinking, these notes espouse a theory of perspective that attempts to go beyond traditional subjectivist theories. For this purpose they expound the suppositions and foundations of this new theory, among which are the real and not the subjective character of perspective as well as the true role of the individuals in his/her relationship with the real.